OCENA ZEWNĘTRZNA A SAMOOCENA – ROZBIEŻNOŚCI I PUNKTY STYCZNE - Mihułka, Krystyna (Neofilolog, 2019)
The aim of this article is to discuss two types of evaluation of students’ language skills: external evaluation (objective) and self-assessment (subjective). The article presents the results of the study conducted among students of German Philology at the University of Rzeszów. The language proficiency level of respondents was assessed three times by means of certified language tests and a self-assessment questionnaire developed in accordance with the CEFR guidelines (2001). The data provided the answer to the main research question: whether and to what extent the students’ self-assessment corresponds to their results achieved in the standardized tests.